2008
DOI: 10.1007/s00464-008-9880-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of a colonoscope for distal duodenal stent placement in patients with malignant obstruction

Abstract: Background Stent placement in the distal duodenum or proximal jejunum with a therapeutic gastroscope can be difficult, because of the reach of the endoscope, loop formation in the stomach, and flexibility of the gastroscope. The use of a colonoscope may overcome these problems. Objective To report our experience with distal duodenal stent placement in 16 patients using a colonoscope. Methods Multicenter, retrospective series of patients with a malignant obstruction at the level of the distal duodenum and proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…In a previous study using the gastroscope, SEMS insertion to distal duodenum or proximal jejunum failed in more than half of all cases, and the colonoscope was used for successful SEMS placement in these cases [6]. Our study showed similar results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In a previous study using the gastroscope, SEMS insertion to distal duodenum or proximal jejunum failed in more than half of all cases, and the colonoscope was used for successful SEMS placement in these cases [6]. Our study showed similar results.…”
Section: Discussionsupporting
confidence: 92%
“…Median survival was 153 days, which is comparable to ours (134 days), but stent patency was not reported in this study [6].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations